SEED VITALITY OF SUNFLOWER INBRED LINES AS INFLUENCED BY CLIMATIC FACTORS AND SEED SIZE - Krstić, Miloš; Ovuka, Jelena; Gvozdenac, Sonja; Butaš, Daliborka; Ćuk, Nemanja; Babec, Brankica; Cvejić, Sandra (Journal on Processing and Energy in Agriculture, 2023)
Climate changes inevitably affect plant production, but it is difficult to predict direct impact on vitality (germination) of a produced seed. This is very important issue, since seed germination is a crucial stage in a life cycle of plants. The aim of this work was to determine the impact of three factors on seed germination of four sunflower inbred lines: i) genotype, ii) climate conditions in a production year, and iii) seed size obtained during a unitary process of processing (larger and smaller seeds). The germination was examined in a Standard laboratory test, six months after the processing and natural breaking of dormancy. Seed were produced in two consecutive years, under different climatic conditions (sum of precipitation, mean monthly temperatures and air humidity during flowering). Collected data was analyzed using three-way ANOVA, and correlation analysis. The coefficient of variation was 8.19%. Significantly higher seed germination, in average, was in 2020 (92%) compared to 2021 (85%). Genotype had the highest influence on significant differences between germination values, followed by production year, i.e. climate conditions, and their interaction. The effect of seed size was not statistically significant, regardless on the tested inbred line.
Keywords: climatic factors, germination, inbred lines, seed size, sunflower.